Exploring the presence of cognitive social capital in Philippine communities - Catharine E. Adaro (Philippine Institute for Development Studies (PIDS), 2018)
Public trust in government and the strengthened solidarity are the aspects of social capital that can increase community participation in the development programs run by the government. Social capital is a resource that exists in relationships, interactions, communications, and mutual cooperation. In this study the cognitive social capital is discussed and measured using two proxies, trust and solidarity. The presence of the different forms of social capital - bridging, bonding and linking - in different levels of local governance (i.e. provincial, municipal, barangay) was also explored utilizing social capital measurement instruments patterned after the SC-IQ tool developed by the World Bank. Findings reveal that compare to city/municipal leaders and most people in the community (generalized trust), household respondents give higher regard to barangay and provincial officials in terms of honestly and and trustworthiness.
Keywords: 330; social capital; cognitive social capital; trust; generalized trust; solidarity; local governance; bridging social capital; bonding social capital; linking social capital